SEJARAH DESA MOPUSI KECAMATAN LOLAYAN TAHUN 1935-1947 - Dinda Kunsi; Zaldy Karmudji2 (Jambura History and Culture Journal, 2021)
This study aims to study the history of Mopusi Village, Lolayan District, 1935-1947. In this paper, the historical method consists of four stages, namely heuristics, critical analysis, interpretation, and historiography. In addition to using the historical method, they also use social science related to writing and interviews. Social science as a tool to answer what is a problem in a historical writing. This scientific work talks about the history of the village of Mopusi starting in 1935-1947, and explains about the origin of the residents forming a settlement until it became the village of Mopusi. It also describes the situation, government, population, and the socio-cultural life of the people in Mopusi village.